A fractional model of Casson fluid with ramped wall temperature: Engineering applications of engine oil. Issue 6 (25th May 2021) - Arif, Muhammad; Kumam, Poom; Kumam, Wiyada; Khan, Ilyas; Ramzan, Muhammad
Abstract: This study is focused to discuss the applications of non‐Newtonian fluid in engineering problems. In this article magneto‐hydrodynamics Casson fluid have taken with ramped temperature along an infinite plate with oscillations. In addition, in the present study we have considered the effect of porous media, chemical reaction, and radiation. Mostly, non‐Newtonian fluids uses for the lubrication purposes such as, engine oil, grease, and so forth. In the present study engine oil EO is selected as base fluid due to enormous applications in engineering. To enhance the rate of heat transfer two nanoparticles molybdenum disulfide (MoS2 ) and graphene oxide (GO) dispersed in EO. To transform the classical model into time fractional model Caputo–Fabrizio derivative have been used. To obtain the exact solutions for the proposed problem the Laplace transform is used. The solutions are depicted through graphs for various parameters to show the influence on fluid flow. Finally, we have compared the rate of heat transfer using different nanoparticles. It is worth noting that by using (MoS2 ) nanoparticle the heat transfer of engine oil can be enhanced up to 6.35% and by adding GO in regular engine oil the heat transfer can be enhanced up to 5.49%.